2021
DOI: 10.1186/s12905-021-01520-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of access to electricity, female education, and public health expenditure on female health outcomes: evidence from SAARC-ASEAN countries

Abstract: Background The importance of the status of female health should have research priority due to the unique medical needs of women. Hence this paper attempts to explore the nexus of access to electricity, female education, and public health expenditure with female health outcomes in the SAARC-ASEAN countries. Methods Using the data of 2002–2018, and applying the cross-sectional dependence test, Modified Wald test, Wooldridge test, the Panel corrected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Similar findings were also obtained by Mondal and Shitan [ 19 ] for 91 countries, Raghupathi and Raghupathi [ 45 ] for 26 OECD countries. Rahman and Alam [ 46 ] found that female education increased female life expectancy and reduced female mortality rates in SAARC-ASEAN countries. Furthermore, Rahman and Alam [ 47 ] identified the negative influence of female education on the child mortality rate in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar findings were also obtained by Mondal and Shitan [ 19 ] for 91 countries, Raghupathi and Raghupathi [ 45 ] for 26 OECD countries. Rahman and Alam [ 46 ] found that female education increased female life expectancy and reduced female mortality rates in SAARC-ASEAN countries. Furthermore, Rahman and Alam [ 47 ] identified the negative influence of female education on the child mortality rate in Bangladesh.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite LPG access and gender equality yielding a non-significant result, in the further analysis a significant association was found between LPG access and the education about health effects for women. This relationship is well documented, but we could establish that the relationship is specific to health effects and for India [118,119]. The results are useful for the design of future schemes for generating tangible gendered benefits in India.…”
Section: Further Analysis With Lpg Accessmentioning
confidence: 80%
“…Many studies have been conducted providing strong evidence to justify living conditions as basic social determinants of persons’ physical and mental health outcomes [ 28 , 41 ]. A recent study showed that women’s life expectancy had been positively influenced by electricity access and female education and negatively associated with women’s adult mortality rate [ 42 ]. Thus, experiencing barriers to accessing healthcare plays the role of an intermediate factor that is affected by living standard and hence deteriorates women’s health outcomes.…”
Section: Discussionmentioning
confidence: 99%